2018
DOI: 10.1016/j.mineng.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The current state and future directions of percolation leaching in the Chinese mining industry: Challenges and opportunities

Abstract: China is one of the most rapidly growing economies in the world and this growth is underpinned by growing demand for natural resources to meet base and precious metals and energy requirements. Even though China is currently the largest producer of several mined commodities, such as gold and the rare earth elements, meeting the future demands for metal consumption will require China to either develop new mining projects or increase material imports. In terms of nuclear energy requirements the country still depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 96 publications
1
30
0
1
Order By: Relevance
“…The need to manage sulfidic waste rocks and tailings is becoming an increasingly urgent issue. Safety issues (e.g., tailings dam failures), air pollution (e.g., dust generation), and water contamination (e.g., Minerals 2019, 9, 401 2 of 15 mine drainage) constitute the main concerns [8][9][10]. Many researchers have worked on the development of sustainable and eco-friendly solutions to eliminate or minimize the risks related to the disposal of mine tailings.…”
Section: Introductionmentioning
confidence: 99%
“…The need to manage sulfidic waste rocks and tailings is becoming an increasingly urgent issue. Safety issues (e.g., tailings dam failures), air pollution (e.g., dust generation), and water contamination (e.g., Minerals 2019, 9, 401 2 of 15 mine drainage) constitute the main concerns [8][9][10]. Many researchers have worked on the development of sustainable and eco-friendly solutions to eliminate or minimize the risks related to the disposal of mine tailings.…”
Section: Introductionmentioning
confidence: 99%
“…They could also be used as raw material in the production of concrete composites [1,2]. As the remaining metals contained in the solid phase of tailings, not recovered at the time of production, represent potential resources, reprocessing could be an alternative to global metal consumption from the perspective of sustainable mining [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, adding an appropriate amount of surfactant featuring specific structure has been found to be a potential way to promote the leaching [12]. Previous studies showed that the addition of surfactants such as polysorbate (Tween), p-octyl polyethylene glycol phenyl ether (emulsifier OP), o-phenylenediamine (OPD), or potassiumamyl xanthate (KAX), could result in the enhanced bioleaching of cobalt ore [13], arsenopyrite [14], marmatite [15], or zinc sulphide, respectively [16].…”
Section: Introductionmentioning
confidence: 99%